Analisis Manajemen Risiko dan Efisiensi Operasional Terhadap Kinerja Keuangan Perbankan - Vanessa S Angelina; Thia Margaretha Tarigan; Christianus Yudi Prasetyo (Journal of Business and Economics Research (JBE), 2026)
This study aims to analyze the effect of Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Operating Expenses to Operating Income (BOPO) on the financial performance of banking institutions listed on the Indonesia Stock Exchange during the 2020–2024 period. This study uses secondary data obtained from published financial reports and applies multiple linear regression analysis with the help of SPSS software. The results of the F test show that NPL, LDR, and BOPO together have a significant effect on financial performance as measured by Return on Assets (ROA), with an R Square value of 0.790. This means that 79.0% of the variation in ROA can be explained by these three variables, while the remaining 21.0% is influenced by other factors not included in the model, such as interest rates, inflation, and bank size. Partially, LDR affects ROA, this can be seen from the LDR significance value of 0.036 <0.05. The BOPO variable also has a partial effect on ROA, as evidenced by its significant value of 0.000 < 0.005. Meanwhile, the NPL variable does not affect ROA, as its significant value is 0.084 > 0.05. The positive impact of LDR indicates that effective fund distribution increases profits, while the negative impact of BOPO highlights the critical role of operational efficiency in maintaining financial performance. These findings suggest that bank management maintains a balance between liquidity and operational efficiency to optimize profits. Further research is recommended to incorporate external macroeconomic variables for a more comprehensive understanding.